Watch Out for the “Living Dead”: Cell-Free Enzymes and Their Fate - Baltar, Federico (Frontiers in Microbiology, 2018)
Microbes are the engines driving biogeochemical cycles. Microbial extracellular enzymatic activities (EEAs) are the “gatekeepers” of the carbon cycle. The total EEA is the sum of cell-bound (i.e., cell-attached), and dissolved (i.e., cell-free) enzyme activities. Cell-free enzymes make up a substantial proportion (up to 100%) of the total marine EEA. Although we are learning more about how microbial diversity and function (including total EEA) will be affected by environmental changes, little is known about what factors control the importance of the abundant cell-free enzymes. Since cell-attached EEAs are linked to the cell, their fate will likely be linked to the factors controlling the cell’s fate. In contrast, cell-free enzymes belong to a kind of “living dead” realm because they are not attached to a living cell but still are able to perform their function away from the cell; and as such, the factors controlling their activity and fate might differ from those affecting cell-attached enzymes. This article aims to place cell-free EEA into the wider context of hydrolysis of organic matter, deal with recent studies assessing what controls the production, activity and lifetime of cell-free EEA, and what their fate might be in response to environmental stressors. This perspective article advocates the need to go “beyond the living things,” studying the response of cells/organisms to different stressors, but also to study cell-free enzymes, in order to fully constrain the future and evolution of marine biogeochemical cycles.